Theoretical Computer Science - Proceedings Of The 10th Italian Conference On Ictcs '07 - Giuseppe F Italiano, Eugenio Moggi, Luigi Laura (World Scientific Publishing Company, 2007)
Many researchers from different countries converged at the 10th Italian Conference on Theoretical Computer Science (ICTCS 2007) to discuss recent developments in theoretical computer science. The volume contains all contributed papers selected for presentation with the invited lectures delivered. The subjects of this book range from logical and mathematical aspects of computing, design and analysis of algorithms, to semantics of programming languages.